Longevity, Health, and Housing Risk Management in Retirement - PIERRE‐CARL MICHAUD; PASCAL ST‐AMOUR (The Journal of Finance, 2026)
ABSTRACT Annuities, long‐term care insurance, and reverse mortgages remain puzzlingly unpopular to manage post‐retirement longevity, health, and housing price risks. We use a flexible life‐cycle model structurally estimated with a unique stated‐preference survey experiment of Canadian households to understand why. Key factors include high risk aversion, concern over long‐run risks, strong discounting of valuation in disability states, imperfect housing substitutability, and bequest motives. The remaining disinterest is accounted for by information frictions and inertia. We also document evidence of public insurance crowding out, spousal co‐insurance, and responsiveness to product bundling.